1986
DOI: 10.1111/j.1600-051x.1986.tb01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival health and frequency of tooth brushing in the beagle dog model

Abstract: The aim of this experiment was to study clinical parameters when 3 different frequencies of plaque removal were applied to healthy gingivae in the beagle dog model. The maxillary first, second and third premolars of 12 beagle dogs, at the start of the experiment 2 years of age, were, after a thorough cleaning, submitted to daily plaque removal during a pre-experimental period of 8 weeks. At the start of the experiment, the dogs were distributed into 3 groups of 4 dogs each: one group was brushed 7 times a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 32 publications
2
26
1
1
Order By: Relevance
“…The present study showed that there is a relationship between frequency of brushing and efficacy of brushing in the rate of accumulation of dental plaque and calculus in dogs when a standard brushing protocol is used. 3 In the dogs with gingivitis (following professional cleaning, 8-weeks of daily brushing, then no oral hygiene provided for a 4-week period prior to the start of the brushing trial), daily brushing was required to return to, and maintain the gingiva in a healthy state over a 24-week period. Brushing EOD did not maintain clinically healthy gingiva in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that there is a relationship between frequency of brushing and efficacy of brushing in the rate of accumulation of dental plaque and calculus in dogs when a standard brushing protocol is used. 3 In the dogs with gingivitis (following professional cleaning, 8-weeks of daily brushing, then no oral hygiene provided for a 4-week period prior to the start of the brushing trial), daily brushing was required to return to, and maintain the gingiva in a healthy state over a 24-week period. Brushing EOD did not maintain clinically healthy gingiva in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that many dog owners would prefer not to have to brush their dog's teeth, this study was performed to determine the optimal frequency of brushing. 3 Brushing EOD in a separate study was insufficient to maintain healthy gingiva. 1 In another study, conducted in dogs with gingivitis, daily brushing was required to return to and maintain gingival health.…”
Section: Introductionmentioning
confidence: 99%
“…It is of value to distinguish, apart from gingival health, between 3 different experimental disease entities in animals namely: experimental gingivitis, artificial periodontal defects immediately after creation, and stable artificial periodontal defects after a period of healing (Jansen 1982), In a previous article (Corba et al,-1986), the influence of plaque removal on artificial periodontal defects immediately after creation in beagle dogs was investigated. The results showed that in such a situation, brushing, 7 times a week was necessary to establish gingival health, Tromp et al, (1986) did a comparable experiment testing different frequencies of plaque removal on healthy gingivae in beagle dogs. The results indicated that in such a situation, brushing 3 times a week was sufficient to maintain gingival health.…”
mentioning
confidence: 97%
“…Il a été montré qu'il faut au moins effectuer un brossage trois fois par semaine pour maintenir des gencives saines chez un chien jeune mais qu'une fré-quence d'une fois par semaine ne le permet pas (Tromp et al, 1986a). Cependant, lorsqu'une gingivite est déjà installée, seul un brossage quotidien peut permettre de rétablir des gencives saines (Tromp et al, 1986b).…”
Section: Hygiène Bucco-dentaireunclassified